2014
DOI: 10.1002/bjs.9670
|View full text |Cite
|
Sign up to set email alerts
|

Value of CT–PET after neoadjuvant chemoradiation in the prediction of histological tumour regression, nodal status and survival in oesophageal adenocarcinoma

Abstract: CT-PET following nCRT for OAC has poor prognostic and discriminatory value for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 41 publications
(92 reference statements)
4
27
1
Order By: Relevance
“…Large recent studies (n 5 88-284) reported that the predictive value of a clinical complete response based on postchemoradiation 18 F-FDG PET (either or not combined with endoscopic biopsy) for pathCR was low (range, 20%-64%) (11,12,14), a finding that was confirmed in the current study (45%). In other FIGURE 2.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Large recent studies (n 5 88-284) reported that the predictive value of a clinical complete response based on postchemoradiation 18 F-FDG PET (either or not combined with endoscopic biopsy) for pathCR was low (range, 20%-64%) (11,12,14), a finding that was confirmed in the current study (45%). In other FIGURE 2.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, seeking more powerful predictors for pathCR is of high relevance to modern personalized cancer care for which the aim is to tailor treatment to the individual patient. 18 F-FDG PET is a well-established imaging modality for the initial staging of esophageal cancer and restaging after preoperative chemoradiotherapy for the detection of distant (interval) metastases (10)(11)(12). The value of 18 F-FDG PET to predict response to preoperative chemoradiotherapy in patients with esophageal cancer has been studied extensively with wide varying methodologies and conflicting results (6,10,13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cervino et al 29 described a 91% 18-month disease-free survival for patients with a negative FDG PET-CT, who did not undergo surgery postneoadjuvant treatment. However, the reported data are heterogeneous; for example, Elliot et al 30 found that CMR on post-CRT FDG PET-CT and CPR did not correlate. This may partly relate to study timing, as radiation-induced oesophagitis can mimic residual active disease and limit the utility of interim and post-treatment PET-CT.…”
Section: Oesophageal Carcinomamentioning
confidence: 99%